Working Memory for Signs with Poor Visual Resolution: fMRI Evidence of Reorganization of Auditory Cortex in Deaf Signers - Andin, Josefine (Cereb Cortex, 2021)
Stimulus degradation adds to working memory load during speech processing. We investigated whether this applies to sign processing and, if so, whether the mechanism implicates secondary auditory cortex. We conducted an fMRI experiment where 16 deaf early signers (DES) and 22 hearing non-signers performed a sign-based n-back task with three load levels and stimuli presented at high and low resolution. We found decreased behavioral performance with increasing load and decreasing visual resolution, but the neurobiological mechanisms involved differed between the two manipulations and did so for both groups. Importantly, while the load manipulation was, as predicted, accompanied by activation in the frontoparietal working memory network, the resolution manipulation resulted in temporal and occipital activation. Furthermore, we found evidence of cross-modal reorganization in the secondary auditory cortex: DES had stronger activation and stronger connectivity between this and several other regions. We conclude that load and stimulus resolution have different neural underpinnings in the visual–verbal domain, which has consequences for current working memory models, and that for DES the secondary auditory cortex is involved in the binding of representations when task demands are low.